Targeting TLR4 Signaling to Blunt Viral-Mediated Acute Lung Injury - Shirey, Kari Ann; Blanco, Jorge C. G.; Vogel, Stefanie N. (Frontiers in Immunology, 2021)
Respiratory viral infections have been a long-standing global burden ranging from seasonal recurrences to the unexpected pandemics. The yearly hospitalizations from seasonal viruses such as influenza can fluctuate greatly depending on the circulating strain(s) and the congruency with the predicted strains used for the yearly vaccine formulation, which often are not predicted accurately. While antiviral agents are available against influenza, efficacy is limited due to a temporal discon-nect between the time of infection and symptom development and viral resistance. Uncontrolled, influenza infections can lead to a severe inflammatory response initiated by pathogen-associated molecular patterns (PAMPs) or host-derived danger-associated molecular patterns (DAMPs) that ultimately signal through pattern recognition receptors (PRRs). Overall, these pathogen-host inter-actions result in a local cytokine storm leading to acute lung injury (ALI) or the more severe acute respiratory distress syndrome (ARDS) with concomitant systemic involvement and more severe, life threatening consequences. In addition to traditional antiviral treatments, blocking the host's innate immune response may provide a more viable approach to combat these infectious pathogens. The SARS-CoV-2 pandemic illustrates a critical need for novel treatments to counteract the ALI and ARDS that has caused the deaths of millions worldwide. This review will examine how antagonizing TLR4 signaling has been effective experimentally in ameliorating ALI and lethal infection in challenge models triggered not only by influenza, but also by other ALI-inducing viruses.